Self-compacting shrinkage compensating concrete and preparation method thereof

By acid modification, graphene modification and graft modification of basalt fibers, the interface bonding strength with cement stone is improved, and the problem of easy cracking of concrete is solved and the mechanical properties of concrete are significantly improved.

CN116143462BActive Publication Date: 2025-02-11SICHUAN JINGYIDA ENG INSPECTION CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310199531.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-04
Publication Date
2025-02-11
Estimated Expiration
2043-03-04

AI Technical Summary

Technical Problem

Existing concrete is prone to cracking during hardening, mainly due to the poor interfacial bonding performance of basalt fibers and concrete, resulting in the need to improve the mechanical properties.

Method used

Through the steps of acid modification, graphene modification and graft modification, basalt fibers are modified to increase their surface roughness and specific surface area, and to improve their interface bonding strength with cement stone.

Benefits of technology

The modified basalt fibers are evenly dispersed in the concrete, which significantly improves the compressive strength and split tensile strength of the concrete, thereby improving the overall mechanical properties of the concrete.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of concrete, and specifically discloses a self-compacting shrinkage compensating concrete and a preparation method thereof, wherein the self-compacting shrinkage compensating concrete comprises the following raw materials in parts by weight: 330-360 parts of cement; 80-100 parts of fly ash; 60-80 parts of mineral powder; 950-1050 parts of crushed stone; 600-700 parts of fine sand; 40-60 parts of expansion agent; 4-6 parts of water reducer; 160-180 parts of water; and 20-40 parts of modified basalt fiber. The self-compacting shrinkage compensating concrete of the present application has the advantages of low shrinkage and good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a self-compacting shrinkage compensating concrete and a preparation method thereof. Background Art

[0002] Concrete refers to a composite material formed by mixing cement as a binder and sand and stone as aggregates. Concrete will shrink in volume in the early stage of setting or during the hardening process. It is generally divided into plastic shrinkage, chemical shrinkage, drying shrinkage and carbonization shrinkage. When the tensile stress generated by shrinkage exceeds its tensile strength, concrete will crack. In order to alleviate this situation, producers will add expansion agents such as UEA and ZY to the concrete system, so that the concrete will expand slightly during the hardening process, which is conducive to offsetting most of the shrinkage of the concrete and reducing the cracking of the concrete.

[0003] In the related technology, basalt fibers are added to concrete. When cracks appear in the concrete, the shrinkage force will be transmitted to the basalt fibers. The basalt fibers spanning the cracks can play a certain role in resisting the formation of cracks, thereby reducing the shrinkage rate.

[0004] Regarding the above-mentioned related technologies, since the surface of basalt fiber is smooth and the activity is poor, the interface bonding performance between the added basalt fiber and concrete is poor, and therefore, the mechanical properties of concrete need to be improved. Summary of the invention

[0005] In order to improve the mechanical properties of concrete, the present application provides a self-compacting shrinkage compensating concrete and a preparation method thereof.

[0006] In the first aspect, the present application provides self-compacting shrinkage compensating concrete, which adopts the following technical solution:

[0007] The self-compacting shrinkage compensating concrete comprises the following raw materials in parts by weight:

[0008] 330-360 parts of cement;

[0009] 80-100 parts of fly ash;

[0010] 60-80 parts of mineral powder;

[0011] 950-1050 parts of crushed stone;

[0012] 600-700 parts of fine sand;

[0013] 40-60 parts of expansion agent;

[0014] 4-6 parts of water reducing agent;

[0015] 160-180 parts of water;

[0016] 20-40 parts of modified basalt fiber;

[0017] The preparation method of the modified basalt fiber comprises the following steps:

[0018] Acid modification, mixing basalt fiber and dilute sulfuric acid solution uniformly, heating, soaking, solid-liquid separation, washing, and drying to obtain pretreated basalt fiber;

[0019] Graphene modification, dispersing graphene oxide in water, adding a first aminosilane coupling agent, mixing evenly, adjusting the pH to be acidic, and obtaining a modifier after the reaction is completed, soaking the pretreated basalt fiber in the modifier, taking it out, and drying it to obtain graphene oxide modified fiber;

[0020] Graft modification, dissolving the second aminosilane coupling agent in water, adding graphene oxide modified fiber and nano-silica, mixing evenly, heating under an inert gas atmosphere, adding an appropriate amount of ethanol, and after the reaction is completed, separating the solid and liquid, washing with water, and drying to obtain modified basalt fiber.

[0021] By adopting the above technical solution, soaking basalt fiber in dilute sulfuric acid can increase the roughness and activity of the basalt fiber surface. On the one hand, acid etching makes the basalt fiber surface scaly and produces a large number of micropores, increasing the surface roughness and specific surface area of ​​the basalt fiber, and playing an anchoring role at the same time. On the other hand, the hydrogen ions in the acid solution react with the oxides on the surface of the basalt fiber, increasing the number of Si-OH groups on the surface of the basalt fiber. Graphene oxide contains a large number of functional groups such as carboxyl and hydroxyl groups, which form chemical bonds with basalt fibers through coupling agents, increasing the roughness of the fiber surface. Oxygen-containing functional groups are also conducive to chemical reactions with cement stone matrix, improving the interfacial bonding strength between basalt fiber and cement stone; in the grafting modification step, nano-silicon dioxide is grafted to the surface of basalt fiber through coupling agents, or grafted to the surface of graphene oxide, further increasing the roughness of the fiber surface, and also improving the interfacial bonding strength between basalt fiber and cement stone, thereby improving the mechanical properties of concrete. Unmodified basalt fibers are easily aggregated through hydrogen bonding and are unevenly dispersed. After the basalt fibers are modified in the present application, the probability of their aggregation can be greatly reduced, which is beneficial for the uniform dispersion of the basalt fibers in the concrete, thereby improving the mechanical properties of the concrete.

[0022] Optionally, in the graphene modification step, the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:(0.02-0.04):(0.02-0.06):(30-50).

[0023] By adopting the above technical solution, under the above ratio, graphene oxide can be grafted onto the surface of basalt fiber through the first aminosilane coupling agent.

[0024] Optionally, in the graphene modification step, the pH is adjusted to 3.5-4.5.

[0025] By adopting the above technical solution, after the basalt fiber is treated with an acid solution, an acidic attachment environment is provided for the silane coupling agent, so that the hydrolyzable groups of the silane coupling agent undergo a hydrolysis reaction to completely form silanols, further enhancing the modification effect.

[0026] Optionally, in the grafting modification step, the mass ratio of the graphene oxide modified fiber, the second aminosilane coupling agent, nano-silica and water is 1:(0.03-0.05):(0.1-0.15):(8-10).

[0027] By adopting the above technical solution, under the above ratio, nano silicon dioxide can be grafted onto the surface of basalt fiber through the second aminosilane coupling agent.

[0028] Optionally, in the grafting modification step, the temperature is heated to 65-80° C. and the reaction is carried out for 20-35 minutes.

[0029] By adopting the above technical solution, heating promotes the rapid reaction and shortens the modification time.

[0030] Optionally, the first aminosilane coupling agent is selected from any one of N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl) -γ-aminopropyltriethoxysilane, and N-β (aminoethyl) -γ-aminopropylmethyldiethoxysilane, and the second aminosilane coupling agent is the same as the first aminosilane coupling agent.

[0031] By adopting the above technical solution, the above three aminosilane coupling agents have high reaction activity, can increase the chain structure on the fiber surface, and improve the bonding force between the fiber and the cement stone.

[0032] Optionally, the basalt fiber has a length of 5-8 mm and a diameter of 10-15 μm.

[0033] Optionally, the molar concentration of the dilute sulfuric acid is 1-2 mol / L.

[0034] In a second aspect, the present application provides a method for preparing self-compacting shrinkage compensating concrete, which adopts the following technical solution: The method for preparing self-compacting shrinkage compensating concrete comprises the following steps:

[0035] Step 1, mixing cement, fly ash and mineral powder evenly to obtain a first mixture;

[0036] Step 2, mixing fine sand and crushed stone evenly to obtain a second mixture;

[0037] Step 3, mixing the expansion agent, water reducing agent and water uniformly to obtain an admixture solution;

[0038] Step 4: Evenly mix the first mixture, the second mixture, the admixture solution and the modified basalt fiber to obtain self-compacting shrinkage compensating concrete.

[0039] By adopting the above technical scheme, the present application uses acid modification to increase the surface roughness and specific surface area of ​​basalt fiber, and grafts graphene oxide and nano-silicon dioxide to the surface of basalt fiber through a coupling agent, thereby further increasing the surface roughness of the fiber, improving the interface bonding strength between basalt fiber and cement stone, and improving the mechanical properties of concrete.

[0040] In summary, the present application has the following beneficial effects: since the present application adopts acid modification to increase the surface roughness and specific surface area of ​​basalt fiber, and graphene oxide and nano-silicon dioxide are respectively grafted to the surface of basalt fiber through a coupling agent, the surface roughness of the fiber is increased, the interface bonding strength between basalt fiber and cement stone is improved, and the mechanical properties of concrete are improved. DETAILED DESCRIPTION

[0041] The present application is further described in detail below in conjunction with embodiments.

[0042] Preparation example of modified basalt fiber

[0043] Preparation Example 1

[0044] The modified basalt fiber, the preparation method thereof comprises the following steps:

[0045] Acid modification: 10 kg of basalt fiber and sufficient dilute sulfuric acid solution were mixed and stirred evenly, the length of the basalt fiber was 4 mm, the diameter was 8 μm, the molar concentration of the dilute sulfuric acid was 0.5 mol / L, heated to 50 ° C, soaked for 1.5 hours, filtered, washed with deionized water for 3 times, and dried to obtain pretreated basalt fiber;

[0046] Graphene modification, dispersing graphene oxide in water, adding a first aminosilane coupling agent, mixing and stirring evenly, adjusting the pH to 3, reacting for 1 hour, obtaining a modifier, soaking the pretreated basalt fiber in the modifier for 1 hour, taking it out, and drying it to obtain graphene oxide modified fiber, the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:0.02:0.02:20;

[0047] Graft modification, dissolve the second aminosilane coupling agent in water, add graphene oxide modified fiber and nano-silica, mix and stir evenly, heat to 60°C under a nitrogen atmosphere, add 0.1 kg of ethanol, react for 40 minutes, filter, wash 3 times with deionized water, and dry to obtain modified basalt fiber. The mass ratio of graphene oxide modified fiber, the second aminosilane coupling agent, nano-silica and water is 1:0.03:0.1:15, and the second aminosilane coupling agent and the first aminosilane coupling agent are both KH550.

[0048] Preparation Example 2

[0049] The modified basalt fiber, the preparation method thereof comprises the following steps:

[0050] Acid modification: 10 kg of basalt fiber and sufficient dilute sulfuric acid solution were mixed and stirred evenly, the length of the basalt fiber was 5 mm, the diameter was 10 μm, the molar concentration of the dilute sulfuric acid was 1 mol / L, heated to 50 ° C, soaked for 1 hour, filtered, washed with deionized water 3 times, and dried to obtain pretreated basalt fiber;

[0051] Graphene modification: dispersing graphene oxide in water, adding the first aminosilane coupling agent, mixing and stirring evenly, adjusting the pH to 3.5, reacting for 1.5 hours, obtaining a modifier, soaking the pretreated basalt fiber in the modifier for 1.5 hours, taking it out, and drying it to obtain graphene oxide modified fiber, wherein the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:0.02:0.04:30;

[0052] Graft modification, dissolve the second aminosilane coupling agent in water, add graphene oxide modified fiber and nano-silica, mix and stir evenly, heat to 65°C under a nitrogen atmosphere, add 0.1 kg of ethanol, react for 35 minutes, filter, wash 3 times with deionized water, and dry to obtain modified basalt fiber. The mass ratio of graphene oxide modified fiber, the second aminosilane coupling agent, nano-silica and water is 1:0.04:0.12:8, and the second aminosilane coupling agent and the first aminosilane coupling agent are both N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane.

[0053] Preparation Example 3

[0054] The modified basalt fiber, the preparation method thereof comprises the following steps:

[0055] Acid modification: 10 kg of basalt fiber and sufficient dilute sulfuric acid solution were mixed and stirred evenly, the length of the basalt fiber was 6 mm, the diameter was 12 μm, the molar concentration of the dilute sulfuric acid was 1.5 mol / L, heated to 55°C, soaked for 1 hour, filtered, washed with deionized water 3 times, and dried to obtain pretreated basalt fiber;

[0056] Graphene modification: dispersing graphene oxide in water, adding the first aminosilane coupling agent, mixing and stirring evenly, adjusting the pH to 4, reacting for 1.5 hours, obtaining a modifier, soaking the pretreated basalt fiber in the modifier for 1.5 hours, taking it out, and drying it to obtain graphene oxide modified fiber, wherein the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:0.02:0.06:40;

[0057] Graft modification, dissolve the second aminosilane coupling agent in water, add graphene oxide modified fiber and nano-silica, mix and stir evenly, heat to 70°C under nitrogen atmosphere, add 0.15kg ethanol, react for 30min, filter, wash 3 times with deionized water, and dry to obtain modified basalt fiber, the mass ratio of graphene oxide modified fiber, the second aminosilane coupling agent, nano-silica and water is 1:0.05:0.15:9, and the second aminosilane coupling agent and the first aminosilane coupling agent are both N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane.

[0058] Preparation Example 4

[0059] The modified basalt fiber, the preparation method thereof comprises the following steps:

[0060] Acid modification: 10 kg of basalt fiber and sufficient dilute sulfuric acid solution were mixed and stirred evenly, the length of the basalt fiber was 8 mm, the diameter was 15 μm, the molar concentration of the dilute sulfuric acid was 2 mol / L, heated to 45 ° C, soaked for 2 h, filtered, washed with deionized water 3 times, and dried to obtain pretreated basalt fiber;

[0061] Graphene modification: dispersing graphene oxide in water, adding the first aminosilane coupling agent, mixing and stirring evenly, adjusting the pH to 4.5, reacting for 1.5 hours, obtaining a modifier, soaking the pretreated basalt fiber in the modifier for 1.5 hours, taking it out, and drying it to obtain graphene oxide modified fiber, wherein the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:0.04:0.06:50;

[0062] Graft modification, dissolve the second aminosilane coupling agent in water, add graphene oxide modified fiber and nano-silica, mix and stir evenly, heat to 80°C under nitrogen atmosphere, add 0.15kg ethanol, react for 20min, filter, wash 3 times with deionized water, and dry to obtain modified basalt fiber, the mass ratio of graphene oxide modified fiber, the second aminosilane coupling agent, nano-silica and water is 1:0.04:0.12:10, and the second aminosilane coupling agent and the first aminosilane coupling agent are both N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane.

[0063] Preparation Example 5

[0064] The difference from Preparation Example 3 is that the second aminosilane coupling agent and the first aminosilane coupling agent are both N-β (aminoethyl) -γ-aminopropyltriethoxysilane.

[0065] Preparation Example 6

[0066] The difference from Preparation Example 3 is that the second aminosilane coupling agent and the first aminosilane coupling agent are both N-β (aminoethyl) -γ-aminopropylmethyldiethoxysilane.

[0067] Preparation Example 7

[0068] The difference from Preparation Example 5 is that the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:0.005:0.02:20.

[0069] Preparation Example 8

[0070] The difference from Preparation Example 5 is that the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:0.03:0.02:20.

[0071] Preparation Example 9

[0072] The difference from Preparation Example 5 is that the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:0.04:0.02:20.

[0073] Preparation Example 10

[0074] The difference from Preparation Example 5 is that the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:0.08:0.02:20.

[0075] Comparative Preparation Example 1

[0076] Ordinary unmodified basalt fiber is used.

[0077] Comparative Preparation Example 2

[0078] The difference from Preparation Example 1 is that the preparation method of modified basalt fiber includes the following steps: acid modification, mixing and stirring 10 kg of basalt fiber and a sufficient amount of dilute sulfuric acid solution, the length of the basalt fiber is 4 mm, the diameter is 8 μm, the molar concentration of the dilute sulfuric acid is 0.5 mol / L, heating to 50°C, soaking for 1.5 hours, filtering, washing with deionized water 3 times, and drying to obtain modified basalt fiber.

[0079] Comparative Preparation Example 3

[0080] The difference from Preparation Example 1 is that the preparation method of modified basalt fiber includes the following steps:

[0081] Acid modification: 10 kg of basalt fiber and sufficient dilute sulfuric acid solution were mixed and stirred evenly, the length of the basalt fiber was 4 mm, the diameter was 8 μm, the molar concentration of the dilute sulfuric acid was 0.5 mol / L, heated to 50 ° C, soaked for 1.5 hours, filtered, washed with deionized water for 3 times, and dried to obtain pretreated basalt fiber;

[0082] Graphene modification: disperse graphene oxide in water, add the first aminosilane coupling agent, mix and stir evenly, adjust the pH to 3, react for 1 hour, obtain the modifier, soak the pretreated basalt fiber in the modifier for 1 hour, take it out, and dry it to obtain the modified basalt fiber; the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:0.02:0.02:20.

[0083] Comparative Preparation Example 4

[0084] The difference from Preparation Example 1 is that the preparation method of modified basalt fiber includes the following steps:

[0085] Acid modification: 10 kg of basalt fiber and sufficient dilute sulfuric acid solution were mixed and stirred evenly, the length of the basalt fiber was 4 mm, the diameter was 8 μm, the molar concentration of the dilute sulfuric acid was 0.5 mol / L, heated to 50 ° C, soaked for 1.5 hours, filtered, washed with deionized water for 3 times, and dried to obtain pretreated basalt fiber;

[0086] Graft modification, dissolve the second aminosilane coupling agent in water, add pretreated basalt fiber and nano-silica, mix and stir evenly, heat to 60°C under nitrogen atmosphere, add 0.1kg ethanol, react for 40min, filter, wash 3 times with deionized water, and dry to obtain modified basalt fiber. The mass ratio of pretreated basalt fiber, the second aminosilane coupling agent, nano-silica and water is 1:0.03:0.1:15, and the second aminosilane coupling agent and the first aminosilane coupling agent are both KH550.

[0087] Comparative Preparation Example 5

[0088] The difference from Preparation Example 1 is that the preparation method of modified basalt fiber includes the following steps:

[0089] Graphene modification: dispersing graphene oxide in water, adding a first aminosilane coupling agent, mixing and stirring evenly, adjusting the pH to 3, reacting for 1 hour, obtaining a modifier, soaking the basalt fiber in the modifier for 1 hour, taking it out, and drying it to obtain graphene oxide modified fiber, wherein the mass ratio of basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1:0.02:0.02:20;

[0090] Graft modification, dissolve the second aminosilane coupling agent in water, add graphene oxide modified fiber and nano-silica, mix and stir evenly, heat to 60°C under a nitrogen atmosphere, add 0.1 kg of ethanol, react for 40 minutes, filter, wash 3 times with deionized water, and dry to obtain modified basalt fiber. The mass ratio of graphene oxide modified fiber, the second aminosilane coupling agent, nano-silica and water is 1:0.03:0.1:15, and the second aminosilane coupling agent and the first aminosilane coupling agent are both KH550.

[0091] Example

[0092] Example 1

[0093] The self-compacting shrinkage compensating concrete comprises the following raw materials in parts by weight:

[0094] Cement 330kg;

[0095] Fly ash 100kg;

[0096] Mineral powder 60kg;

[0097] Crushed stone 950kg;

[0098] 600kg fine sand;

[0099] 40kg of expansion agent, which is a magnesium expansion agent with a magnesium oxide content of 86%;

[0100] Water reducing agent 4kg;

[0101] Water 160kg;

[0102] 20 kg of modified basalt fiber, which was prepared in Preparation Example 1;

[0103] The method for preparing self-compacting shrinkage compensating concrete comprises the following steps:

[0104] Step 1, mixing cement, fly ash and mineral powder to obtain a first mixture;

[0105] Step 2, mixing fine sand and crushed stone to obtain a second mixture;

[0106] Step 3, mixing the expansion agent, water reducing agent and water to obtain an admixture solution;

[0107] Step 4: Mix the first mixture, the second mixture, the admixture solution and the modified basalt fiber and stir them evenly to obtain a self-compacting shrinkage compensating concrete.

[0108] Embodiment 2-10

[0109] The difference from Example 1 is that the modified basalt fiber is prepared in sequence from Preparation Examples 2 to 10.

[0110] Embodiment 11

[0111] The difference from Example 8 is that the self-compacting shrinkage compensating concrete includes the following raw materials in parts by weight:

[0112] Cement 350kg;

[0113] Fly ash 90kg;

[0114] Mineral powder 70kg;

[0115] 1000kg of crushed stone;

[0116] 650kg fine sand;

[0117] 50kg expansion agent;

[0118] Water reducing agent 5kg;

[0119] Water 170kg;

[0120] Modified basalt fiber 30kg.

[0121] Example 12

[0122] The difference from Example 8 is that the self-compacting shrinkage compensating concrete includes the following raw materials in parts by weight:

[0123] Cement 360kg;

[0124] Fly ash 80kg;

[0125] Mineral powder 80kg;

[0126] Crushed stone 1050kg;

[0127] 700kg fine sand;

[0128] 60kg expansion agent;

[0129] Water reducing agent 6kg;

[0130] Water 180kg;

[0131] Modified basalt fiber 40kg.

[0132] Comparative Example

[0133] Comparative Examples 1-5

[0134] The difference from Example 1 is that the modified basalt fiber is prepared from Comparative Preparation Examples 1-5 in sequence.

[0135] Performance testing

[0136] Test methods

[0137] Compressive strength and splitting tensile strength: The compressive strength and splitting tensile strength of the concrete of Examples 1-12 and Comparative Examples 1-5 after curing for 28 days were tested in accordance with GB / T 50081-2019 “Standard for Test Methods for Physical and Mechanical Properties of Concrete”. The results are shown in Table 1.

[0138] Table 1 Test results of Examples 1-12 and Comparative Examples 1-5

[0139] Example / Comparative Example No. Compressive strength / MPa Splitting tensile strength / MPa Example 1 60.0 6.05 Example 2 60.3 6.11 Example 3 60.8 6.25 Example 4 60.5 6.18 Example 5 61.3 6.33 Example 6 61.1 6.29 Example 7 60.9 6.21 Example 8 62.0 6.41 Example 9 61.8 6.37 Example 10 61.9 6.39 Embodiment 11 62.7 6.52 Example 12 62.4 6.48 Comparative Example 1 55.1 4.55 Comparative Example 2 55.6 4.71 Comparative Example 3 57.1 5.02 Comparative Example 4 56.8 4.96 Comparative Example 5 57.4 5.18

[0140] Combining Examples 1-12 and Comparative Examples 1-5 and Table 1, it can be seen that Comparative Example 1 uses unmodified basalt fiber, and the compressive strength and splitting tensile strength are the lowest. Comparative Example 2 acid-modifies the basalt fiber, and the compressive strength and splitting tensile strength are improved, indicating that acid modification can improve the interface bonding strength between basalt fiber and cement stone, thereby improving the mechanical properties of concrete; Comparative Example 3 is modified with graphene on the basis of acid modification, and the compressive strength and splitting tensile strength are greatly improved, indicating that the combination of acid modification and graphene modification further improves the interfacial bonding strength between basalt fiber and cement stone. The interface bonding strength is improved, thereby improving the mechanical properties of concrete; Comparative Example 4 is grafted on the basis of acid modification, and the compressive strength and splitting tensile strength are greatly improved, indicating that the combination of acid modification and grafting modification further improves the interface bonding strength between basalt fiber and cement stone, thereby improving the mechanical properties of concrete; Comparative Example 5 is graphene-modified and grafted on basalt fiber, and the compressive strength and splitting tensile strength are greatly improved, indicating that the combination of graphene and grafting modification further improves the interface bonding strength between basalt fiber and cement stone, thereby improving the mechanical properties of concrete; Example 1 At the same time, the basalt fiber was acid-modified, graphene-modified and graft-modified, and the compressive strength and splitting tensile strength were greatly improved, indicating that the combination of acid modification, graphene and graft modification further improved the interface bonding strength between basalt fiber and cement stone, thereby improving the mechanical properties of concrete; the parameters of the preparation method of modified basalt fiber in Examples 2-4 are within the scope of this application, and the compressive strength and splitting tensile strength are slightly improved, indicating that the parameters of the preparation method of modified basalt fiber will affect the mechanical properties of concrete, among which Example 3 has a better effect; Examples 5-6 use different Silane coupling agent, the compressive strength and splitting tensile strength are slightly improved, and the effect of Example 5 is better, indicating that the types of the first aminosilane coupling agent and the second aminosilane coupling agent will affect the performance of the modified basalt fiber, and then affect the mechanical properties of concrete; Examples 7-10 change the mass ratio of pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water, and the compressive strength and splitting tensile strength are changed, and the effect of Example 8 is better, indicating that the raw material ratio in the method for modifying basalt fiber will affect the performance of the modified basalt fiber, and then affect the mechanical properties of concrete.

[0141] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. Self-compacting shrinkage compensating concrete, characterized by: The invention comprises the following raw materials in parts by weight: 330-360 parts of cement; 80-100 parts of fly ash; 60-80 parts of mineral powder; 950-1050 parts of crushed stone; 600-700 parts of fine sand; 40-60 parts of expansion agent; 4-6 parts of water reducing agent; 160-180 parts of water; 20-40 parts of modified basalt fiber; The preparation method of the modified basalt fiber comprises the following steps: Acid modification, mixing basalt fiber and dilute sulfuric acid solution uniformly, heating, soaking, solid-liquid separation, washing, and drying to obtain pretreated basalt fiber; Graphene modification, dispersing graphene oxide in water, adding a first aminosilane coupling agent, mixing evenly, adjusting the pH to be acidic, and obtaining a modifier after the reaction is completed, soaking the pretreated basalt fiber in the modifier, taking it out, and drying it to obtain graphene oxide modified fiber; Graft modification, dissolving the second aminosilane coupling agent in water, adding graphene oxide modified fiber and nano-silicon dioxide, mixing evenly, heating under an inert gas atmosphere, adding an appropriate amount of ethanol, and after the reaction is completed, separating the solid and liquid, washing with water, and drying to obtain modified basalt fiber; In the graphene modification step, the pH is adjusted to 3.5-4.5; in the grafting modification step, the temperature is heated to 65-80° C. and the reaction is carried out for 20-35 minutes; the first aminosilane coupling agent is selected from any one of N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl) -γ-aminopropyltriethoxysilane, and N-β (aminoethyl) -γ-aminopropylmethyldiethoxysilane, and the second aminosilane coupling agent is the same as the first aminosilane coupling agent.

2. The self-compacting shrinkage compensating concrete according to claim 1, characterized in that: In the graphene modification step, the mass ratio of the pretreated basalt fiber, graphene oxide, the first aminosilane coupling agent and water is 1: (0.02-0.04): (0.02-0.06): (30-50).

3. The self-compacting shrinkage compensating concrete according to claim 1, characterized in that: In the grafting modification step, the mass ratio of graphene oxide modified fiber, the second aminosilane coupling agent, nano-silicon dioxide and water is 1: (0.03-0.05): (0.1-0.15): (8-10).

4. The self-compacting shrinkage compensating concrete according to any one of claims 1 to 3, characterized in that: The basalt fiber has a length of 5-8 mm and a diameter of 10-15 μm.

5. The method for preparing the self-compacting shrinkage-compensating concrete according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1, mixing cement, fly ash and mineral powder evenly to obtain a first mixture; Step 2, mixing fine sand and crushed stone evenly to obtain a second mixture; Step 3, mixing the expansion agent, water reducing agent and water uniformly to obtain an admixture solution; Step 4: Evenly mix the first mixture, the second mixture, the admixture solution and the modified basalt fiber to obtain self-compacting shrinkage compensating concrete.

Citation Information

Patent Citations

  • Anti-crack and anti-seepage type bridge hinge joint concrete and construction method thereof

    CN109400072A